Development of Smart Irrigation for Aquahydroponics Using the IoT System at Taman Cangkruan25 (Karapan Network Journal : Journal Computer Technology and Mobile Ad Hoc Network, 2025)
Aquahydroponics is an integration of aquaculture and hydroponics systems that rely on water circulation to carry plant nutrients. However, water quality parameters such as pH, temperature, and water level often fluctuate, affecting fish health and plant growth. The manual systems used by farmers often cause delays in detecting anomalies and inconsistencies in irrigation. This study developed an Internet of Things (IoT)-based smart irrigation system to automate water quality monitoring and nutrient flow control in the Aquahydroponics installation at Taman Cangkruan25. The system utilizes an ESP32 microcontroller integrated with a pH sensor, DS18B20 water temperature sensor, DHT22 air humidity sensor, HC-SR04 ultrasonic water level sensor, and DS3231 RTC module as an irrigation schedule controller. Testing was conducted by monitoring water parameters and evaluating the growth of pakcoy plants and catfish. The results showed that the system could maintain pH within the optimal range of 6.5–7.5, reduce water consumption by up to 40%, and increase plant growth by 20–30% compared to the manual system. The fish survival rate reached 93.33%. The implementation of this system proves the potential of IoT technology in improving the efficiency of sustainable aquaculture through automation and data-based monitoring.
Keywords: Keywords: IoT, smart irrigation, aquahydroponics, water quality monitoring, ESP32.